Carpal Ligament Surgery Before Arthritis - Camus, Emmanuel; Van Overstraeten, Luc.; SpringerLink (Online service) (Paris : Springer Paris : Imprint: Springer, 2013)
Nowadays, it is established that carpal ligamentary lesions may lead to instability and then to carpal arthritis. However, the variety of anatomopathological classifications and the multiplicity of surgical repair techniques reflect the difficulty of conceiving this ligamentary pathology. The clinical analysis and traditional investigation techniques face the complexity of the wrist. Its mechanical complexity is due to the number of synchronized bones in every movement of the hand. The clinical analysis of the wrist is insufficient to precisely measure the mobility of each carpal bone. Paraclinical examinations are also significant for clinical diagnosis. The tools available today range from X-rays to arthroscopy, including arthroCTscan and soon MRI. As concerns repair techniques, their diversity must not hide the fact that a biomechanical and physiological principle is involved and must be identified. This book is the result of a reflection of an expert group in the field of wrist pathology. It attempts to analyze, understand, explain and make comprehensible, if not obvious, the reflections that each practitioner should employ during the diagnosis and treatment of carpal ligamentary lesions. The focus is consciously not on degenerative carpal pathology, which usually enjoys more visibility. We hope that readers will benefit from the fact that fragmented pieces of knowledge are gathered in a single work, that they will find in this beginning synthesis inspiring to rethink a difficult and sometimes thankless surgery and to further the surgical advances of the 21st century.
PART 1: FUNDAMENTALS -- Anatomy of the carpal ligaments -- Biomechanics of the carpus. Application to the ligamentary lesions -- Clinical examination of the wrist -- Imaging of the carpal traumatic instabilities -- MRI Normal Anatomy and lesion of the extrinsic ligaments -- Definition and classification of carpal instabilities -- Radio-carpal rotary instability -- Vertical Instability of the carpus. Axial dislocation and fracture-dislocation: Review of the literature -- Normal arthroscopy of the wrist -- Wrist arthroscopy to study intrinsic ligaments -- Arthroscopic anatomy and lesions of the extrinsic ligaments -- Dynamic arthroscopic testing: false positives and false negatives -- Arthroscopic criterions to date ligamentary trauma -- PART 2: TREATMENT OF LIGAMENTARY LESIONS -- Management of the wrist sprains by the general practitioner -- Role of the surgeon in raising the awareness of first-line general practitioners -- Management of the constitutional painful mediocarpal laxity -- Arthroscopic debridement and pinning: treatment of peri-lunate unstable recent lesions -- Scapho-lunate ligament suture with arthrotomy -- Treatment of scapho-lunate instability with Blatt's capsulodesis -- Treatment of the chronic lesions of the scapho lunate ligament before arthritis -- Berger's dorsal intercarpal capsulodesis in chronic scapho-lunate instability -- Viegas's dorsal scapho-lunate capsulodesis -- Capsulo Fibrodesis. A new therapeutic option to treat scapho-lunate lesion (Garcia-Elias type 2, 3 and 4) with reducible scaphoid and without arthritis -- Brunelli's tenodesis -- Chronic lunotriquetral ligament injuries: arthrodesis or capsulodesis -- Scapho-lunate reconstruction with a bone-tissue-bone graft -- Reduction and Association of the Scaphoid and Lunate (RASL) -- Treatment of chronic, static scapholunate dissociation with the modified Brunelli technique: preliminary results -- Scapho-capitate arthrodesis -- Medico legal aspect of the carpal ligamentary traumatisms -- Socio economic aspect of the carpal ligamentary traumatisms.
Keywords: Medicine; Orthopedic surgery; Surgery; Trauma; Medicine & Public Health; Surgical Orthopedics; Traumatic Surgery; Plastic Surgery